Development of Career Patterns of Civil Servants in the Human Resources Staff Unit of the National Police - Syaifuddin Syaifuddin; Nurliah Nurdin; Mala Sondang Silitonga (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2023)
The existence of civil servants in the National Police institution is something unique and distinctive because in the National Police organization, the position of civil servants is in one organization with the National Police in all units of the National Police in charge of carrying out administrative activities and tasks that require special expertise to support the activities of the National Police. For civil servants of the National Police, personnel regulations apply to the National Police and personnel regulations regulated by BKN. The purpose of this study is to analyze the causes of the lack of optimal implementation of career patterns for civil servants in the Human Resources Staff (SSDM) of the National Police and provide a description related to career pattern models that are more professional and appropriate for civil servants in SSDM Polri which can be used as a career pattern model for National Police Civil Servants. This research uses a mix method approach, quantitative data collection which is then deepened qualitatively through interviews, observations and collection of supporting documents. The result is that the career pattern of civil servants in the Human Resources Staff Work Unit is constrained by human resource management governance in the aspects of planning, organizing, procuring and directing, developing and integrating. A more provective career pattern model obtained from the results of discussion and analysis in this study is the placement of civil servants in predetermined functional and structural positions, the implementation of internships for employees who newly recruited, implementation of performance evaluation for promotion followed by attending education and training in accordance with the field of work, providing space and opportunities to actualize themselves to the duties and responsibilities that given in order to be promoted to the top posotion intended for civil servant after attending a series of education and training for competency development.